Pengembangan Vidio Pembelajaran Berbasis Software Adobe Premiere Pro Dalam Meningkatkan Kemampuan Menyimak Dongeng Mata Pelajaran Bahasa Indonesia - Maria Siska Nabella (Universitas Nusantara PGRI Kediri, 2022)
The aim of this study to improve students’ listening ability on fairy tales in Indonesian language learning at SD Tunas Karya Sunter especially for students who have difficulty in listening fairy tales. The research uses R&D method with ADDIE development model. Then, data collection techniques uses needs analysis and questionnaires given to media experts, material experts, linguists, and students. Based on the results of research, the development of learning videos using Adobe Premiere Pro software in improving listening ability on fairy tales showed the average result of the expert review test was 88.59% Very Good and in the user trial was 97.4% and it can be used in improving listening ability on fairy tales. Suggestion for this research is it needs a long time to create an optimal product.